PEDAGOGICAL ACTIVITY IN THE DEVELOPMENT OF THE COUNTRY ROLE AND IMPORTANCE - MAJITOV A.M; RAXIMOV S.K (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article contains feedback on the importance of pedagogical science in the development of society, the importance of knowledge in the educational process, its content-essence, the role and necessity of pedagogical knowledge in military activities.